Characterization of the complete chloroplast genome of Phalaenopsis lobbii (Orchidaceae), an important horticultural plant in China. Issue 3 (2nd July 2020) - Zhang, Yanping; Chen, Bin; Zheng, Yan; Cao, Yinghui; Wei, Ziling; Zhao, Kai; Zhou, Yuzhen
ABSTACT: An important horticultural moth orchid in China, Phalaenopsis lobbii, has small and lovely flowers with unique labial characteristics. We sequenced the chloroplast genome (cpDNAs) of P. lobbii and analyzed the structural characteristics of its complete cpDNAs sequence. The results showed that P. lobbii had a typical circular double-stranded tetrad structure with the average GC content of 36.60%, and its total length was 144, 607 bp. The complete chloroplast was annotated with 125 genes, eight rRNAs and 38 tRNAs. Phylogenetic tree displayed that P. lobbii was closely related to P. equestris, P. aphrodite subsp. formosana, P. 'Tiny Star' and P. japonica . This published cpDNAs of P. lobbii will provide information for future phylogenetic and artificial breeding of Phalaenopsis .